Evaluating the Accuracy of 3D Point Cloud Data of Elevated Structures Using Terrestrial Laser Scanners at Various Distances - Wan Mohamed Syafuan,; Neza Ismail,; Muhammad Hakim Jazmee Rosmee, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Terrestrial laser scanning (TLS) is a powerful tool for generating detailed 3D models of elevated structures such as bridges, towers, and buildings. However, the quality of the resulting models heavily depends on the setup confi guration of the TLS system. This research evaluates the precision of 3D point cloud data of elevated structures acquired through TLS at different distances. The data processing was performed using Cyclone Register360 software. The study aimed to evaluate the accuracy of point cloud data obtained from various TLS setup locations and compare it with the measurements obtained from a Total Station. Four different distances were used to set the TLS to scan the three elevated structure piers. The acquired data was then processed using Cyclone Register360 software to eliminate noise, visually align, and precisely register the point clouds. The results indicated that shorter distances between TLS setups resulted in more accurate point cloud data, with reduced error rates, highlighting the need to locate the scanner effectively. The study also highlighted the capabilities of Cyclone Register360 in improving the precision of point cloud data through effective data processing techniques. The findings demonstrate the significance of precise scanning distance evaluation in TLS applications to ensure high-quality data capture. It is vital for comprehensive 3D modeling and analysis of elevated structures. These valuable insights apply to specialists in surveying, engineering, and architecture. It offers guidance on the best practices for TLS setups, which can improve the accuracy and reliability of measurements. Further studies should examine the influence of other factors, such as scanning angles and environmental conditions, on the precision of TLS data.